Scalp micro-needling: A new tool in the treatment of alopecia totalis - Savitha L Beergouder; Apoorva Reshme (Wolters Kluwer Medknow Publications, 2020)
Alopecia areata is the most common form of nonscarring alopecia. It may vary from a single round patch to that involving large surface area termed as alopecia totalis (AT). Pediatric age of onset, more extensive disease, and recalcitrance to initial therapies are more challenging to treat and require the synergy of two or more established therapy. Here, we have treated a case of AT with scalp micro-needling with topical steroids.